Risks and complications of neuraxial anesthesia and the use of anticoagulation in the surgical patient - Allen, Douglas J. (Baylor Health Care System, 2002)
Recognition of the risk of thromboembolic phenomena to patients in the postsurgical period has resulted in the practice of administering prophylactic anticoagulant agents to those patients who are at high risk for this complication. Institution of a perioperative anticoagulant or antithrombotic protocol needs to be considered when a regional anesthetic is proposed as part of, or as the total, anesthetic management of the patient. This article reviews current data on the risks involved in the use of neuraxial regional anesthesia in the care of surgical patients in whom prophylactic thromboembolic anticoagulant therapy is planned. Guidelines are established to help the physician minimize the risks of a neuraxial hematoma forming, monitor the patient for this complication, and optimally treat him or her if a hematoma were to occur.